Monitoring Dan Evaluasi Jaringan Drainase Yang Ramah Lingkungan Di Perumahan Villa Delima Mayang Kota Jambi - Mariansyah, Mariansyah; Das, Amsori M; Dony, Wari; Fadlan, Fadlan; Azanna, Dwitya Okky (Jurnal Talenta Sipil, 2024)
The rainy season, which has a fairly high frequency over a long period of time, results in the need for drainage so that the amount of rainwater can be channeled into water bodies and some of it can be used for purposes in daily life. This is so as not to cause inundation and flooding problems. This research aims to analyze the condition of the existing drainage network, calculate runoff discharge, plan infiltration wells for utilizing rainwater in the Villa Delima Mayang housing complex, Jambi City. The method used in this planning uses hydrological analysis calculations including mononobe, pearson III and rational log methods. In planning infiltration wells, it refers to the Indonesian National Standard (SNI) No. 03-2453-2002. The result of the 10 year return period design rainfall is 112.17 mm. the results of the analysis of the carrying capacity show that 9 out of 14 channels are unable to accommodate the 10 year return period design discharge. Next, an absorption well with a diameter of 0.8 meters and a depth of 1.5 meters is planned and placed in a drainage channel that cannot accommodate runoff. The absorption capacity of 1 well is 0.7536 m3.